2011
DOI: 10.1021/jp200824m
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Size of Nanodomains in Calcium Aluminosilicate Glasses

Abstract: Transparent nanostructured glasses show interesting properties for optical fibers or laser beam applications. Binary calcium silicate glasses are known to undergo phase separation in silica-rich compositions. However, adding up to a few mole percent of alumina seems to inhibit the phase separation. By adjusting the amount of alumina added to demixing calcium silicate glasses, we managed to obtain transparent, but nanostructured, glasses with either silica-rich or calcium aluminosilicate-rich nanodomains of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 55 publications
2
51
1
Order By: Relevance
“…As illustrated in Figure 2 , the plots of the nanostructure size versus x+y (ZnO + Ga 2 O 3 concentration) and z (Na 2 O concentration) show exponential trends, as previously observed in the case of the addition of alumina in calcium silicate glasses, [ 47 ] which was explained by the repolymerization of the silicon network and the formation of SiO 2 -rich clusters. [ 43 ] This observation demonstrates the importance of the melt structure in the phase-separation mechanisms. The thermodynamic characteristics of the melts, i.e., the free energy of the system, change and promote the homogeneity or immiscibility of the melt.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As illustrated in Figure 2 , the plots of the nanostructure size versus x+y (ZnO + Ga 2 O 3 concentration) and z (Na 2 O concentration) show exponential trends, as previously observed in the case of the addition of alumina in calcium silicate glasses, [ 47 ] which was explained by the repolymerization of the silicon network and the formation of SiO 2 -rich clusters. [ 43 ] This observation demonstrates the importance of the melt structure in the phase-separation mechanisms. The thermodynamic characteristics of the melts, i.e., the free energy of the system, change and promote the homogeneity or immiscibility of the melt.…”
Section: Discussionmentioning
confidence: 76%
“…The results clearly show that the nanodomain size follows an exponential law, as previously observed in the case of the addition of alumina in calcium aluminate glasses. [ 43 ] As a consequence, the average size of the phase separation can be predicted. Interestingly, for compositions with a GeO 2 content less than 80%, the phase-separation type evolves from nucleation-growth to spinodal, as illustrated in the bottom left of Figure 2 .…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 99%
“…Given that SEM revealed glass‐in‐glass phase separation over a μm range in some of the silica‐rich compositions initially attempted [marked by shaded boxes in Fig. (a)], and that phase separation has been observed in related systems, such as Y aluminate and even Ca AS glasses, transmission electron microscopy (TEM) was utilized to confirm the homogeneous single‐phase character of our six Sc AS glasses also down to the lowest length‐scale attainable by our instrument (≲10 nm). Figure displays representative TEM images recorded from four glass powders, each one examined across >30 fragments.…”
Section: Resultsmentioning
confidence: 93%
“…In order to study submicronic microstructures, we have studied a second glass composition with a small percentage of alumina [40,22], denoted as quaternary glass in Table 1 and subsequently. Since the quaternary diagram has not yet been characterized in the literature, we determined the dome temperature for this composition by thermal treatments at different temperatures, followed by a rapid quench in water.…”
Section: Glass Composition and Preparationmentioning
confidence: 99%
“…Because of the limited range of sizes that are observable during a t 1/3 evolution, a more successful approach for controlling the microstructure size consists in leveraging thermodynamics instead of kinetics, by changing the composition in order to modify the value of the critical temperature. Martel et al [22], for example, found that the typical size of phase-separated droplets decreased exponentially with alumina content in calcium aluminosilicate glasses. A similar strategy has been applied to metallic glasses [23].…”
Section: Introductionmentioning
confidence: 99%